1999
DOI: 10.1590/s0103-90161999000300030
|View full text |Cite
|
Sign up to set email alerts
|

Water deficit in relation to leaf and stem anatomy of Eucalyptus camaldulensis Dehn. shoots cultivated in vitro

Abstract: Shoots of E. camaldulensis seedlings from three distinct provenances were submitted to three different levels of in vitro water deficit induced by the addition of sorbitol in the growth media. Transversal sections from the leaf blades and stems were anatomically analysed using the historesin inclusion technique. Shoots from the different provenances presented distinct responses to the treatments. The Gilbert River provenance was the most sensible. The basic alterations found on the anatomical structure in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Two types of mesophyll has been recognized, isobilateral in Callistemon viminalis and Eucalyptus camaldulensis or dorsiventral in the other taxa ( Figure 2) in agreement with the work of [11]. Souza et al (1999) [20] mentioned that mesophyll of Eucalyptus camaldulensis is bifacial. while in Eugenia pyriformis the mesophyll was dorsiventral [21], but [3,4] stated that leaves in Eucalyptus and Eugenia sometimes show the two structures depending on the case of these leaves if are vertical or horizontal.…”
Section: Transverse Sections Of Laminasupporting
confidence: 87%
“…Two types of mesophyll has been recognized, isobilateral in Callistemon viminalis and Eucalyptus camaldulensis or dorsiventral in the other taxa ( Figure 2) in agreement with the work of [11]. Souza et al (1999) [20] mentioned that mesophyll of Eucalyptus camaldulensis is bifacial. while in Eugenia pyriformis the mesophyll was dorsiventral [21], but [3,4] stated that leaves in Eucalyptus and Eugenia sometimes show the two structures depending on the case of these leaves if are vertical or horizontal.…”
Section: Transverse Sections Of Laminasupporting
confidence: 87%
“…The higher LMA may account for a greater investment of resources in structural components of acacia foliages. Anatomically, phyllodes have thick cell wall and a two-layered palisade parenchyma at the abaxial and adaxial surfaces (Duarte andwolf 2005, Leroy et al 2009), while the thickest sclerophyllous-true leaves of E. camaldulensis consist of a single layer of palisade parenchyma at the abaxial side (Souza et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The irrigation issue has been discussed in the eucalyptus forests. Souza, Gonçalves and Almeida (1999) indicated that the morphophysiological variations existing in plants of E. camaldulensis under different water deficit conditions. Research has shown that irrigation yields positive results in terms of growth increments (Özkurt et al, 2002).…”
Section: Introductionmentioning
confidence: 95%